The Open Book of Social Innovation - Murray, Robin; Caulier-Grice, Julie; Mulgan, Geoff (Young Foundation, NESTA, 2010)
This book is about the many ways in which people are creating new and more effective answers to the biggest challenges of our times: how to cut our carbon footprint; how to keep people healthy; how to end poverty. It describes the methods and tools for innovation being used across the world and across the different sectors – the public and private sectors, civil society and the household – and in the overlapping fields of the social economy, social entrepreneurship and social enterprise. It draws on inputs from hundreds of organisations around the world to document the many methods currently being used. In other fields, methods for innovation are well-understood. In medicine, science, and business, there are widely accepted ideas, tools and approaches. But despite the richness and vitality of social innovation, there is little comparable in the social field. Most people trying to innovate are aware of only a fraction of the methods they could be using. This book provides a first mapping of these methods and of the conditions that will enable social innovation to flourish.
On aurait pu mettre cet ouvrage dans chacune des sections de la boîte à outils tant il découpe et met en évidence une foule de méthodes qui pourront vous épauler tout au long du développement de votre projet.
Keywords: Libre accès; UK

New frontiers in social innovation research - Nicholls, Alex; Caulier-Grice, Julie; Gabriel, Madeleine (Palgrave Macmillan, 2015)
Interest in social innovation continues to rise, from governments setting up social innovation 'labs' to large corporations developing social innovation strategies. Yet theory lags behind practice, and this hampers our ability to understand social innovation and make the most of its potential. This collection brings together work by leading social innovation researchers globally, exploring the practice and process of researching social innovation, its nature and effects. Combining theoretical chapters and empirical studies, it shows how social innovation is blurring traditional boundaries between the market, the state and civil society, thereby developing new forms of services, relationships and collaborations. It takes a critical perspective, analyzing potential downsides of social innovation that often remain unexplored or are glossed over, yet concludes with a powerful vision of the potential for social innovation to transform society. It aims to be a valuable resource for students and researchers, as well as policymakers and others supporting and leading social innovation.
Présentation des différentes dimensions de l’innovation sociale, et d’études de cas sur la théorie de l’innovation sociale, son histoire, son impact, comment la repenser, la produire, l’intelligence collective pour la produire. Études de cas sur la stratégie de la ville de Séoul et dans une favela pacifiée à Rio de Janeiro; et l’utilisé des réseaux (Ex. Inde). p. 198-201 : Challenge Grant comme méthode d’innovation collective
Keywords: Idéation; dialogue et maillage; Libre accès

New frontiers in social innovation research - Nicholls, Alex; Caulier-Grice, Julie; Gabriel, Madeleine (Palgrave Macmillan, 2015)
Interest in social innovation continues to rise, from governments setting up social innovation 'labs' to large corporations developing social innovation strategies. Yet theory lags behind practice, and this hampers our ability to understand social innovation and make the most of its potential. This collection brings together work by leading social innovation researchers globally, exploring the practice and process of researching social innovation, its nature and effects. Combining theoretical chapters and empirical studies, it shows how social innovation is blurring traditional boundaries between the market, the state and civil society, thereby developing new forms of services, relationships and collaborations. It takes a critical perspective, analyzing potential downsides of social innovation that often remain unexplored or are glossed over, yet concludes with a powerful vision of the potential for social innovation to transform society. It aims to be a valuable resource for students and researchers, as well as policymakers and others supporting and leading social innovation.
Info sur le livre ajoutée par Geneviève
Keywords: Libre accès

The Open Book of Social Innovation - Murray, Robin; Caulier-Grice, Julie; Mulgan, Geoff (Young Foundation, NESTA, 2010)
This book is about the many ways in which people are creating new and more effective answers to the biggest challenges of our times: how to cut our carbon footprint; how to keep people healthy; how to end poverty. It describes the methods and tools for innovation being used across the world and across the different sectors – the public and private sectors, civil society and the household – and in the overlapping fields of the social economy, social entrepreneurship and social enterprise. It draws on inputs from hundreds of organisations around the world to document the many methods currently being used. In other fields, methods for innovation are well-understood. In medicine, science, and business, there are widely accepted ideas, tools and approaches. But despite the richness and vitality of social innovation, there is little comparable in the social field. Most people trying to innovate are aware of only a fraction of the methods they could be using. This book provides a first mapping of these methods and of the conditions that will enable social innovation to flourish.
Keywords: Libre accès; UK

The Open Book of Social Innovation - Murray, Robin; Caulier-Grice, Julie; Mulgan, Geoff (2010)
This volume – part of a series of methods and issues in social innovation – describes the hundreds of methods and tools for innovation being used across the world, as a first step to developing a knowledge base.
Chapitre. 3